Combining Prosodic-Pragmatic Training and Free Commentary to Develop Intonation Skills in Italian FL: The Case of Information-Seeking Polar Questions - Nicora, Francesca (Journal of Audiovisual Translation, 2024)
Prosodic skills are a fundamental component of language learning but are notoriously difficult to develop due to their highly variable nature. In the burgeoning research field of didactic audiovisual translation, free commentary (FC) appears to be a less-studied modality of revoicing in the foreign language classroom. The main aim is to investigate the suitability of FC as a reinforcement activity for improving FL intonation skills. This paper presents an experimental study conducted at the University of Galway with undergraduate students studying Italian as a FL. The research design has a multi-stage structure. It consists of prosodic-pragmatic training, during which the experimental group learnt how to pronounce a polar question to ask for information, while the control group attended traditional conversation classes. A discourse completion task (DCT) was administered before and after the training. Secondly, both groups were required to complete FC to reinforce their intonation skills. Data analysis of DCT and FC was carried out within the autosegmental-metrical theoretical framework and the tone and break indices system. The results corroborate previous studies on the effectiveness of training and highlight the didactic value of FC in reinforcing FL intonation skills. The novelty of this study lies in the combination of the disciplines of prosody in FL acquisition, didactic audiovisual translation, and intonational phonology. Lay summary The prosodic features of speech (e.g. intonation, rhythm, stress) are of paramount importance for successful communication and are a cornerstone of second language acquisition. However, it has been recognised that language learners still struggle to develop prosodic competence. In recent years, there has been a growing interest in audiovisual translation, i.e. the translation of audiovisual texts, such as films, with subtitling and revoicing (e.g. dubbing, voice-over, audio description). Didactic free commentary is a less studied mode of revoicing that adapts the original dialogue (if any) or renders the image in a foreign language. This paper presents an experimental study conducted at the University of Galway in which a number of undergraduate students used free commentary as a task to improve their prosodic skills in Italian as a foreign language. The main aim was to integrate free commentary into the foreign language classroom in order to help students practise intonation patterns previously learned through prosodic-pragmatic training. The students were divided into two groups. The experimental group received the training, the control group attended traditional conversation classes. Both groups performed a free commentary task. Data collection consisted of a discourse completion task, a production questionnaire used in linguistics and pragmatics to elicit specific target sentences, given to both groups before and after the training, and the free commentary task itself. Data analysis was carried out within the autosegmental-metrical theoretical framework, a method for the description of the use of prosodic features of the voice. The results showed that the experimental group changed the intonation pattern towards the Italian model, while the control group did not show any change. During free commentary task, the experimental subjects were able to use the correct intonation patterns for a specific communicative context; the control group failed to reuse the intonation patterns. This demonstrates the effectiveness of prosodic-pragmatic training and the didactic value of the free commentary as reinforcement activity to improve intonation skills. The originality of this paper is also to link different disciplines, such as contrastive linguistics, audiovisual translation, intonational phonology, with the intention of investigating how learners develop prosodic competence in Italian foreign language.